Stability of Theoretical Solution and Numerical Solution of Nonlinear Differential Equations with Piecewise Delays (Journal of Computational Mathematics, 2005)
This paper is concerned with the stability of theoretical solution and numerical solution of a class of nonlinear differential equations with piecewise delays. At first, a sufficient condition for the stability of theoretical solution of these problems is given, then numerical stability and asymptotical stability are discussed for a class of multistep methods when applied to these problems.
Keywords: Stability; Delay differential equations; Linear multistep methods.